Seismic performances of reinforced concrete frames with wall-like columns - Lim, Chee Leong (2012)
In regions of low to moderate seismic risk, such as Singapore and Malaysia, buildings with relatively weak lateral structural resisting systems are likely to be common. Although ground motions because of long distance earthquakes centred in Sumatra have occurred, there has been no record of earthquake damage in this region. This article compares the results obtained from pushover analyses of six-storey reinforced concrete (RC) frames with experimental observations. The experimental observations of four internal beam-column joints, which were designed according to BS 8110, were summarised. From this, we address the performance of some typical RC frame structures under low seismic loading. By adding about 0.075% of hoop reinforcement in the beam-column joints, one can improve the seismic performance of the frame in the weak direction more significantly than in the strong direction. Also, relatively large joint shear input during low to moderate earthquakes can result in diagonal tension cracking and the building may likely be governed by joint shear failure.